The Effect of Hadith Tarbawi Utilization in Islamic Education on 21st-Century Learning Readiness: The Mediating Roles of Critical Thinking and Religious Commitment - Naila Intania; Muhammad Arif Luthfi; Eli Fitriana; Destriani Destriani; Yuni Hana Lestari (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study addresses the growing demand for 21st-century learning readiness, which requires not only cognitive competence but also ethical and value-based orientation. Within Islamic Education, Hadith Tarbawi is often underutilized as a pedagogical resource, despite its potential to support holistic student development. Therefore, this study aims to examine the effect of Hadith Tarbawi utilization in Islamic Education on students’ 21st-century learning readiness, with critical thinking and religious commitment as mediating variables. This research employed a quantitative explanatory design involving 218 upper secondary students. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The analysis included measurement model evaluation and structural model testing, along with mediation analysis using bootstrapping procedures. The findings reveal that Hadith Tarbawi utilization has a significant positive effect on 21st-century learning readiness, both directly and indirectly. It significantly enhances students’ critical thinking and religious commitment, which in turn contribute to improved learning readiness. Mediation analysis confirms that both variables act as partial mediators, indicating the integration of cognitive and affective-religious dimensions. These results imply that Hadith Tarbawi, when implemented through contextual and reflective pedagogical approaches, can serve as an effective educational tool aligned with contemporary learning demands. This study contributes to bridging Islamic educational sources with modern competency-based frameworks and offers practical guidance for developing holistic, value-oriented learning models in Islamic Education.